The prospected air quality measurements for further unconventional natural gas developments in China based on the United States experience - Fang, Tao; Zhang, Xiaomeng; Zhang, Jie; Wang, Junfeng; Sun, Qianqian (Frontiers in Environmental Science, 2022)
The technology innovation of the horizontal drilling and the high-volume hydraulic fracturing has promoted the development of unconventional natural gas (UNG) production worldwide, and hence has aroused the public concern about the air pollution it may bring about. In this study, we have provided (1) an overview of the study on air pollutants from UNG emissions in the USA, focusing on both the air pollutant characterization and their related observation technologies/platforms; and (2) the potential air quality measurements of UNG development emerging in China. This study will provide a useful guidance for Chinese environmental researchers and the local governments to deal with related air quality issues.